Neohormones in milk - Ivell, Richard; Anand-Ivell, Ravinder (Elsevier, 2017)
Neohormone systems evolved specifically to regulate those mammalian traits, such as internal fertilization, pregnancy and lactation, which have proved to be central to the success, environmental independence, and adaptability of mammals as a vertebrate group. Neohormones such as oxytocin or relaxin are not only involved in the regulation of mammary gland development and function, but are also significant components of milk itself. Particularly for the latter hormone, it has been shown for the pig that relaxin in the first milk is taken up by the gastrointestinal tract of the offspring, enters the neonatal circulation and can have specific physiological and epigenetic effects on target organs such as the female reproductive system. Nevertheless, there are large gaps in our knowledge and understanding of such lactocrine systems especially in regard to other neohormones, species, and neonatal organ systems.